Awarness on animal welfare handling and transportation elements during festive season among traders in Kedah - Adil, Ibrahim (2022)
Animal welfare is receiving increasing attention from Malaysian society and the international community. The World Organization for Animal Health (WOAH) has developed a standard guideline for animal welfare to be applied by all WOAH member nations. WOAH's animal welfare standards encompass a wide range of animal welfare issues, including animal transport. According to the USDA, 2022, the majority of animals, including those utilised for study or display, will be transported by truck, trailer, aeroplane, or boat at some point in their life. Transport can be a substantial cause of stress for animals; therefore, it is crucial to consider their welfare throughout the process. Animal welfare concerns in Malaysia appear to be on the rise. This trend appears to be growing, maybe because of increased public awareness of animal welfare. The importance of animal welfare during the handling and transport of animals must be assessed with respect to the understanding of farmers, particularly animal traders. This study seeks to determine the degree of knowledge, attitude, and practise (KAP) among animal traders about the welfare of Aidiladha sacrificial animals during handling and transportation, and to develop concrete solutions to solve this issue. The results indicated that majority animal traders in the State of Kedah have a high KAP level, with 85.72% have high knowledge, 94.6% have high attitude, and 98.22% have high practice in animal welfare during handling and transport. Attitude and knowledge variables were also shown to have a relationship with best practises, with the relationship between attitude variables and best practises being particularly high. Consequently, the KAP survey of animal traders reveals the level of animal welfare knowledge during handling and transit. Consequentially, the government's efforts to educate stakeholders and the public about animal welfare must consist of an ongoing enforcement and awareness campaign. Further study needs to be done to assess among others livestock industry player and public opinion on animal welfare practice during handling and transport for government better understanding for better future policy formulation, strategic planning, and animal welfare implementation.